Nuevos aportes al conocimiento de la nidificación de algunas aves del noroeste argentino - Di Giacomo, Alejandro G. (2000)
We present new dat on nesting of 12 bird species of the Yungas (montane forests ) of Salta and Jujuy provinces. We provide information on date, location, size, materials and contents of the nests. The nest and eggs of Atlapetes torquatus, apparently unknown, are described. Most avian species bred in the wet season, but Amazilia chionogaster nested in the dry season.